Effective Strategies For Providing Communication Stimulation For Children With Speech Delay In Preschools - Syaadiah Arifin; Siti Sa'idah; Mohamad Sudi; Nurul Hidayati; Fujiono Fujiono (Sean Institute, 2024)
This study sought to find effective communication stimulation methods for preschoolers with speech impairments. One preschool's 35 children, teachers, and parents were surveyed and interviewed qualitatively. Game-based learning, flashcards, and interactive technology were the most effective methods. The game-based method helps kids correlate words with real activities or objects, improving language comprehension and memory. Visual aids assist youngsters focus and prevent confusion, while learning applications and educational videos provide compelling visual and auditory stimuli to study at their own pace. The strategy also relied on teacher-parent collaboration. Parents' play-based activities at home and school intervention programs accelerated children's speech improvement. However, the study found several limitations, such as keeping short-attention-span children's attention. Overcoming these problems requires more flexible and adaptable strategy improvements. This study recommends a more structured and inclusive intervention approach that can be adjusted to each child's needs including teacher and parent training. Future study should examine how new and innovative technology affect children's language development and how home and school contexts affect it.